STUDI PERENCANAAN INSTALASI PENGOLAHAN LIMBAH LINDI SEBAGAI KONTROL PEMENUHAN BAKU MUTU SESUAI KEPMEN 03/91 (STUDI KASUS PADA TPA SUPIT URANG MALANG) - Chairil Saleh (Media Teknik Sipil, 2012)
Chairil SalehFakultas Teknik Jurusan Teknik Sipil Universitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas, No.246 MalangEmail: chairil@umm.ac.idABSTRACTThe processing of lye waste instalation is a processing lye waste leachate discharged intowater bodies do not pollute the environment .Harm caused leachatecan kill the organisms – organismsif the leachate is discharged directly into water bodies without prior treatment.Need for storage pondsfor leachate treatment plant, and therefore the capacity to design pondsneed to know how the leachate discharges.Required to discharge leachate storage ponds designedto meet the volume of pond water leachate.From the analysis of the leachate discharge obtained by9.43 m3/day. And the production of leachate was 0.8 m3 / day. Levels of waste treatment unit COD= 8960mg / l and BOD5 = 3968.293 mg / l, after going through the waste treatment plant to be COD= 298.67 mg / l and BOD5 = 88.18 mg / l. From the processing of these three levels in an alreadymeets the standard group III cross section pond 03/91.Keywords : Water leachate , storage ponds , COD and BOD5.